X-RAY SPECTRAL ANALYSIS IN X-RAY FLUORESCENCE IMAGING FOR BREAST CANCER DETECTION - Ren, Liqiang (My University, 2016)
The knowledge of X-ray spectrum plays a major role in exploiting and optimizing the X-ray utilizations, especially in biomedical application fields. Over the past decades, extensive research efforts have been made in better characterizing the X-ray spectral features in experimental and simulation studies. The objectives of this dissertation are to investigate the applications of X-ray spectral measurement and analysis in X-ray fluorescence (XRF) and micro-computed tomography (micro-CT) imaging modalities, to facilitate the development of new imaging modalities or to optimize the imaging performance of currently available imaging systems. The structure and primary discoveries of this dissertation are as follows: after a brief introduction of the objectives of this dissertation in Chapter 1, Chapter 2 gives a comprehensive background including electromagnetic properties, various applications, and different generation mechanisms of X-rays and their interactions with matter, X-ray spectral measurement and analysis methods, XRF principles and applications for cancer detection, and micro-CT system. Considering relatively high fluorescence production probability and sufficient penetrability of gold Kα fluorescence signals, Chapter 3 establishes a theoretical model of a gold nanoparticle (GNP) K-shell XRF imaging prototype consisting of a pencil-beam X-ray for excitation and a single collimated spectrometer for XRF detection. Then, the optimal energy windows of 66.99±0.56keV and 68.80±0.56keV for two gold Kα fluorescence peaks are determined in Chapter 4. Also, the linear interpolation method for background estimation under the Kα fluorescence peaks is suggested in this chapter. Chapters 5 and 6 propose a novel XRF based imaging modality, X-ray fluorescence mapping (XFM) for the purpose of breast cancer detection, especially emphasizing on the detection of breast tumor located posteriorly, close to the chest wall musculature. The mapping results in these two chapters match well with the known spatial distributions and different GNP concentrations in 2D/3D reconstructions. Chapter 7 presents a method for determining the modulation transfer function (MTF) in XRF imaging modality, evaluating and improving the imaging performance of XFM. Moreover, this dissertation also investigates the importance of X-ray spectral measurement and analysis in a rotating gantry based micro-CT system. A practical alignment method for X-ray spectral measurement is first proposed using 3D printing technology in Chapter 8. With the measured results and corresponding spectral analysis, Chapter 9 further evaluates the impact of spectral filtrations on image quality indicators such as CT number uniformity, noise, and contrast to noise ratio (CNR) in the micro-CT system using a mouse phantom comprising 11 rods for modeling lung, muscle, adipose, and bones (various densities). With a baseline of identical entrance exposure to the imaged mouse phantom, the CNRs are degraded with improved beam quality for bone with high density and soft tissue, while are enhanced for bone with low density, lung, and muscle. Finally, Chapter 10 summarizes the whole dissertation and prospects the future research directions.
Keywords: X-ray spectral analysis, X-ray fluorescence, Breast cancer detection